2017
DOI: 10.1177/2333794x17712637
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Hypertension: Provider Perspectives

Abstract: Pediatric hypertension is a risk for adult cardiovascular disease, making early detection important. The prevalence of pediatric essential hypertension is rising due to the increased prevalence of obesity. Though guidelines for screening, diagnosis, evaluation, and management are available, there are barriers to accurate diagnosis of pediatric hypertension, including lack of knowledge and complexity of blood pressure standards. We aimed to gain insights into reasons for low rates of diagnosis and treatment fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…Similar results were seen in an earlier multicentre study that used insurance claim data . While some studies that have examined the management of hypertensive children in primary care cite provider's unfamiliarity and/or discomfort in treating childhood HTN , another explanation could be provider ambivalence related to underappreciation of the significance of abnormal BP in the paediatric age group.…”
Section: Childhood Htn Is Common Yet Infrequently Treatedsupporting
confidence: 76%
“…Similar results were seen in an earlier multicentre study that used insurance claim data . While some studies that have examined the management of hypertensive children in primary care cite provider's unfamiliarity and/or discomfort in treating childhood HTN , another explanation could be provider ambivalence related to underappreciation of the significance of abnormal BP in the paediatric age group.…”
Section: Childhood Htn Is Common Yet Infrequently Treatedsupporting
confidence: 76%
“…Moreover, pediatric hypertension is associated with target organ damage, including left ventricular hypertrophy, increased carotid-intima media thickness and microalbuminuria [2,3]. Nevertheless, several studies have suggested that knowledge, screening, diagnosis, and management for pediatric hypertension is profoundly insufficient among most physicians [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Parents, even those whose children have received a diagnosis, may be confused about the diagnosis simply because clinicians are confused about the diagnosis. 5 , 14 , 18 , 19 Medical providers need to engage parents and children in the diagnostic process better. For example, parents could be informed that BP values can vary a lot, which is why an average across 3 appointments is needed.…”
Section: Implications For Current Practicementioning
confidence: 99%